2022
DOI: 10.1039/d2gc01160c
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the mechanism of milk protein as an efficient lignin blocker for boosting the enzymatic hydrolysis of lignocellulosic substrates

Abstract: The residual lignin in pretreated biomass significantly hinders the bio-conversion of cellulose into monosaccharides. In this work, a low-cost non-enzymatic protein from defatted milk was proposed to block the lignin-enzyme...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Owing to the complexity of lignin and cellulase structures, it is necessary to develop a comprehensive approach that can reveal the interaction between enzyme molecules and lignin or cellulose from different perspectives and levels. Based on the advanced analytical techniques mentioned above, as well as extensive literature research and experimental results from our research group, 13,30,32,35 we propose a comprehensive multidimensional nondestructive spectroscopic analysis technique. This technique aims to achieve in situ and real-time analysis of the interfacial interactions between lignin and cellulase by investigating adsorption-desorption processes (SPR), quantifying the magnitude of binding forces (AFM), and determining the contribution of major forces (FLS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the complexity of lignin and cellulase structures, it is necessary to develop a comprehensive approach that can reveal the interaction between enzyme molecules and lignin or cellulose from different perspectives and levels. Based on the advanced analytical techniques mentioned above, as well as extensive literature research and experimental results from our research group, 13,30,32,35 we propose a comprehensive multidimensional nondestructive spectroscopic analysis technique. This technique aims to achieve in situ and real-time analysis of the interfacial interactions between lignin and cellulase by investigating adsorption-desorption processes (SPR), quantifying the magnitude of binding forces (AFM), and determining the contribution of major forces (FLS).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations and gain further insight into the interaction mechanism of lignin-cellulase, FLS was used to investigate the binding ability of cellulase and conformation changes during their interaction. In our previous studies, Zhao et al 30 and Huang et al 35 introduced the commonly used analytical technique of fluorescence spectroscopy from the field of physical chemistry into the study of the mechanism of action of lignin-cellulase. This approach allows for the analysis of conformational changes in cellulases and provides insights into their binding capacity and thermodynamic properties in relation to lignin.…”
Section: Introductionmentioning
confidence: 99%
“…It is a building material rather than a reserve material like starch, and the combined presence of cellulose, hemicellulose and lignins determines its high resistance to biodegradation. In order to increase the susceptibility of lignocellulosic biomass to enzymatic degradation, an additional stage is introduced to the process of the production of cellulosic bioethanol—it is referred to as pretreatment [ 2 , 3 ]. Its task is to increase the share of the amorphous areas in cellulose and a degradation of hemicellulose, as well as a removal of lignins [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another strategy consists in incorporating specific enzyme cocktails, mainly composed by glucanases, that impart a regioselective treatment over the cellulose chain, mostly onto the β-1,4 glucosidic bonds, but also in other regions due to the heterogeneity of commercial enzyme cocktails [ 20 , 21 ]. However, the presence of lignin may limit the accessibility of these enzymes to the cellulose chain due to steric effects, lowering the yield of the whole operation or, otherwise, requiring longer treatment times [ 22 , 23 ]. This lower accessibility of the enzymes in lignin-containing fibers was already observed by Espinosa et al and significantly lower yields of fibrillation were found for enzymatic treatments compared to mechanical treatments [ 24 ].…”
Section: Introductionmentioning
confidence: 99%